Diagnostic Accuracy of Two Molecular Tools for Diagnosis of Congenital Chagas Disease - Bisio, Margarita María Catalina (2021)
Background and Objective: The real prevalence of congenital Chagas disease is undefined because of difficulties in the detection of Trypanosoma cruzi by microscopic examination. The aim of this study was to determine the diagnostic accuracy of two molecular diagnostic tools, qPCR and LAMP, in the diagnosis of congenital Chagas disease in a clinical setting. Methods: To this end, we conducted a prospective cohort study in a tertiary care center, of infants under 9 months of age, born in Buenos Aires to women with Chagas disease. Blood samples were collected for microscopic examination and molecular diagnosis at baseline. If negative, infants were followed up until 9 months of age to determine a final diagnosis by serology. In-house qPCR and LAMP previously validated were challenged as index tests. Results: A total of 154 participants were potentially eligible, 120 of whom were enrolled. Finally, 102 (66.2%) of them fulfilled the follow-up. The diagnosis of congenital Chagas disease was confirmed in 13 infants and excluded in 89. Both the sensitivity and specificity of the qPCR were 100.0% (95% confidence interval 75.3–100.0 and 95% confidence interval 95.9–100.0, respectively), whereas the sensitivity and specificity of LAMP were 69.2% (95% confidence interval 38.6–90.9) and 100% (95% confidence interval 95.9–100.0), respectively. Conclusions: The qPCR agreed with the current diagnostic algorithm, and was a reliable and sensitive tool to detect congenital Chagas disease earlier, providing an appropriate and timely identification of infected infants requiring treatment. LAMP was able to detect congenital Chagas disease in infected infants by naked-eye visualization in accordance with a microscopic examination. The advantages of molecular diagnostic tools should be taken into account by the health system to improve congenital Chagas disease diagnosis.